Radiation Dose to the Contralateral Breast and Effectiveness of Superflab in Dose Reduction during Treatment of Breast Cancer by Cobalt-60 External Beam - Chiuyo, Julius S.; Msaki, Peter K.; Makundi, Ismail N. (Tanzania Journal of Science, 2020)
Radiation therapy for breast cancer inevitably results in scattered dose to contralateral breast. Breast tissues being highly sensitive to ionizing radiations, the chance of the contralateral breast developing second cancer after radiation therapy is high. This study investigated dose to contralateral breast and its reduction by superflab during the course of breast cancer radiation therapy. A thorax breast phantom constructed from tissue-equivalent materials and diodes (type IVD2 1137) were used to measure surface doses to the contralateral breast. The mean doses received by the contralateral breast were 2.2% and 7.1% of the prescribed dose of 200 cGy for 5 × 5 cm2 and 10 × 10 cm2 field sizes, respectively. These dose values were mostly comparable to and slightly higher than the dose values reported in the literature. The average reduction of dose to contralateral breast with superflab was 65.6%, in the range of 49 to 100%. The differences between doses with and without superflab were significant at p < 0.05. The superflab was more effective for larger field sizes than smaller. In view of this enormous advantage in dose reduction, this approach should clinically be tested for routine applications in breast cancer radiation therapy at hospitals in Tanzania.